2021
DOI: 10.1016/j.jval.2021.02.012
|View full text |Cite
|
Sign up to set email alerts
|

To What Extent Do Patient Preferences Differ From General Population Preferences?

Abstract: In some countries including Germany, value sets based on general population preferences are not acceptable for decision-makers in healthcare because the impact of the reference group-general population versus patients-on utility decrements is questioned. The objective of this study was to explore potential differences in patient versus general population health preferences and a way of combining both preferences in economic evaluation.Methods: EQ-5D-5L general population preferences were available from nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 24 publications
0
6
2
1
Order By: Relevance
“…These findings suggest that potential future value sets for the OxCAP-MH elicited from the general population are likely to represent well also the direct preferences of people with lived experience of mental ill-health. These results somewhat contradict the findings that patient preferences differ from preferences derived from the general population for the EQ-5D-5L items [ 10 ]. In the study by Ludwig et al, 2021, patients in the EQ-5D-5L study gave more importance to mobility, self-care, or usual activities and less importance to pain/discomfort and anxiety/depression compared to the general population [ 10 ].…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…These findings suggest that potential future value sets for the OxCAP-MH elicited from the general population are likely to represent well also the direct preferences of people with lived experience of mental ill-health. These results somewhat contradict the findings that patient preferences differ from preferences derived from the general population for the EQ-5D-5L items [ 10 ]. In the study by Ludwig et al, 2021, patients in the EQ-5D-5L study gave more importance to mobility, self-care, or usual activities and less importance to pain/discomfort and anxiety/depression compared to the general population [ 10 ].…”
Section: Discussioncontrasting
confidence: 80%
“…These results somewhat contradict the findings that patient preferences differ from preferences derived from the general population for the EQ-5D-5L items [ 10 ]. In the study by Ludwig et al, 2021, patients in the EQ-5D-5L study gave more importance to mobility, self-care, or usual activities and less importance to pain/discomfort and anxiety/depression compared to the general population [ 10 ]. The differential findings between the two studies could be explained by the specific perception of mental health itself and the difference between health-related quality of life and capabilities as evaluative spaces.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Higher utility scores are occasionally seen in patients compared to the general public. More recently, Ludwig and colleagues [ 25 ] demonstrated patient preferences that differed from general public preferences, where patients reported more concern about functional aspects than about pain and anxiety when compared to the general public. Another recent study [ 26 ] showed minimal differences in utility scores between general public and patient samples when utility scores were collected using the same health states for both groups.…”
Section: Discussionmentioning
confidence: 99%
“…One approach to estimating HSUV in this circumstance is the use of direct HSUV elicitation techniques, such as time trade-off, standard gamble, or discrete choice experiments. The problem with this solution is that patients have a tendency to over-value their own health state relative to opinions of the general public from whom valuation sets for indirect HSUV instruments are derived (Peeters & Stiggelbout 2010; Ludwig et al 2021). This risks inducing a ceiling effect with high HSUV estimates for the pretreatment condition and limited potential for clinically significant gain.…”
Section: Discussionmentioning
confidence: 99%